2003
DOI: 10.1111/j.1553-2712.2003.tb00608.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Race/Ethnicity and Desirable Social Characteristics on Physicians' Decisions to Prescribe Opioid Analgesics

Abstract: Patient race/ethnicity did not influence physicians' predispositions to treatment plans in clinical vignettes. Even knowing that the patient had a high-prestige occupation and a primary care provider only minimally increased prescribing of opioid analgesics for conditions with few objective findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
93
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 44 publications
1
93
2
Order By: Relevance
“…The influence of physician-patient racial and ethnic concordance on patient care has been consistently documented for decades, [16][17][18][19][20] and may partially explain some of the disparities found. Previous studies have demonstrated that despite their best efforts, physicians sometimes struggle to perform as unbiased operators, often allowing their own cultural and social constructs to partially dictate their approach to patient care, including their medication prescribing.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of physician-patient racial and ethnic concordance on patient care has been consistently documented for decades, [16][17][18][19][20] and may partially explain some of the disparities found. Previous studies have demonstrated that despite their best efforts, physicians sometimes struggle to perform as unbiased operators, often allowing their own cultural and social constructs to partially dictate their approach to patient care, including their medication prescribing.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies have shown relatively poor adherence to evidencebased guidelines for the treatment of acute LBP among physicians, especially among general practitioners with more years of clinical experience. Other case vignette studies in medical research have focused on the professional judgments of social workers regarding the need for institutional care [26], the opioid prescribing practices of emergency room physicians [27], and the effect of racial bias in medical decision-making [28]. Case vignettes can test a number of hypothesized variables thought to influence decision-making, and predictive variables can include both experimental factors (randomized factors systematically altered in different versions of the vignette), and respondent factors (variables reflecting attitudes and characteristics of the decision-maker).…”
Section: Methodsmentioning
confidence: 99%
“…The mostly null findings in this study could also be interpreted as promising evidence that physicians' decisionmaking is not significantly influenced by race/ethnicity when other clinical and family context variables are held constant (such as socioeconomic status, parental employment, family composition, treatment motivation, etc.). For example, in another study examining the role of adult patient race/ ethnicity on decisions to prescribe medication, investigators found that patient characteristics such as occupation and perceived reliability with follow-up were more significantly associated with physician decision-making than the patient's race/ethnicity [27].…”
Section: Discussionmentioning
confidence: 99%
“…Yet independent of race, physicians' perceptions of patients' education and physical activity preferences were significant predictors of treatment recommendations [26]. Tamayo-Sarver and colleagues found that "socially desirable patient characteristics" associated with occupation, relationship with primary care doctor, and reliability of follow-up were significantly associated with opioid prescription rates, but race/ethnicity was not [27].…”
Section: Racial/ethnic Disparities In Children's Mental Health Carementioning
confidence: 99%
See 1 more Smart Citation